A revision of the taxonomic status of Pseudocordylus capensis (Reptilia: Cordylidae) - Herselman, Y.M.(Yolande Mariana) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1991.